Between opera and the Lied - ‘Tre sonetti di Petrarca’ by Franz Liszt - Wojtczak, Ziemowit (Interdisciplinary Studies in Musicology, 2018)
Franz Liszt composed his songs in the time when Europe was at the peak of the development of the Romantic form - das Lied. However, it seems that not all of Liszt’s songs should be discussed from this perspective, pointing at least at significant influences of the 19th century Italian opera. The second version of a set of Tre sonetti di Petrarca reflects not only some changes in the composer’s technique or style, but above all, constitutes an evidence of certain tendencies in perceiving vocal technique and the development of Italian and European vocal aesthetics. It might be assumed that, even though the music construction of the second version of the Sonnets - particularly in the layer of melody of the vocal part - brings to mind the Italian operatic aria in its almost purest form, the deeply emotional musical interpretation of Petrarch’s most beautiful love lyrics seems to strongly derive from the already shaped German Romantic song. On the whole, the masterpiece is a bit eclectic, which in the light of Liszt’s reference to the past (belcanto form of an Italian aria, Renaissance lyrics) constitutes - as it could be called today - the author’s postmodern reinterpretation.